ANALYSIS OF THE MARKET OF INNOVATIVE TECHNOLOGIES FOR THE PRODUCTION OF ELECTRIC CARS BY TESLA - YUZYK, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Investigate the current state of development of electric cars, especially Tesla company and outline the prospects for its further development. Analyzed the task of the scientific work consider the role and place of electric cars in the transport system; to analyze the technical and economic features of electric cars; analysis of global and Ukrainian production of electric cars and to analyze the potential and competitiveness of electric cars in comparison with cars with internal combustion engines; program development prospects of electric cars based on methods of stimulating electric car markets in different countries of the world.
Keywords: electric cars; Tesla; brand